Intensive and Explanatory Statistical Analysis of the Relationship Between Inorganic Phosphate Content and Antioxidant Activity in Fresh and Canned Fruit Juices - Al-Salman, Fadheela; Redha, Ali Ali; Al-Zaimoor, Zahra (Iraqi Journal of Science, 2022)
The inorganic phosphate content and antioxidant activity of fresh fruit juices and canned fruit juices commonly consumed in Bahrain were compared. The fruits considered in this study were kiwi, guava, black grape, strawberry, apple, and pineapple. The inorganic phosphate content of the juices was determined by a colorimetric method using a UV/VIS spectrophotometer. Among the fresh juices, the highest inorganic phosphate content was measured for black grape juice (17.330 ±0.068 mg/L), and among the canned juices, the highest inorganic phosphate was measured for black grape canned juice too (16.020 ±0.141 mg/L, brand 3). The antioxidant activity was determined in-vitro by measuring the percentage of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity of the juices. Among the fresh juices, the highest antioxidant activity was measured for fresh guava juice (95.98 ±0.15%). Among the canned juices, the highest antioxidant was measured for black grape canned juice (two brands: 88.69 ±0.05 and 90.49 ±0.12%). According to the inferential statistical analysis (normality assumption tests and one-way ANOVA), no statistically significant correlation was found between inorganic phosphate content and antioxidant activity (Pearson correlation coefficient = 0.279, p-value = 0.263) at a 5% significance level.